Controlled preparation and characterization of Pt-Rh/Al 2 O 3 bimetallic catalysts for reactions in reducing conditions - Hérault, Nelly (2016)
Pt-Rh bimetallic catalysts on alumina support were prepared according to three different techniques, one leading to random deposition of the two metals at the support’s surface, the two others, namely the organometallic grafting and the colloidal route, favoring the formation of bimetallic particles with strong Pt-Rh interactions. Catalysts were characterized by ICP, H2 chemisorption, TPR, FTIR of chemisorbed CO and NO-CO. Then they were evaluated in cyclohexane dehydrogenation and methylcyclopentane hydrogenolysis reactions. Strong interaction between Pt and Rh was demonstrated for catalysts prepared by controlled preparation method, which leads to a strong synergetic effect for methylcyclopentane ring-opening, in terms of activity and selectivity, whereas these interactions do not play a role in cyclohexane dehydrogenation.